A quality improvement initiative using peer audit and feedback to improve compliance. (30th June 2022) - Fridrich, Annemarie; Imhof, Anita; Staender, Sven; Brenni, Mirko; Schwappach, David
Abstract: Background: The Surgical Safety Checklist (SSC) published by the WHO in 2009 is used as standard in surgery worldwide to reduce perioperative patient mortality. However, compliance with the SSC and quality of its application are often not satisfactory. Internal audits and feedbacks seem promising for improving SSC application. Objective: The purpose of this study is to investigate whether an intervention consisting of peer observation and immediate peer feedback can be implemented with high fidelity and acceptance. Method: Data were obtained from a national pilot programme that was initiated in Switzerland in 2018 to measure and improve compliance with the SSC using peer audit and feedback. A total of 11 hospitals with 14 sites implemented the full intervention. Each hospital formed an interprofessional project team that should perform at least 30 observations with feedback on SSC application documented in an observation tool developed specifically for this programme. Since the SSCs of the study hospitals differ greatly regarding checklist items, for each of the three SSC sections standard items were defined: four at Sign In, five at Team Time Out and two at Sign Out. Frequency analyses were performed for initiation characteristics, SSC application at item level, feedback characteristics and programme evaluation. Results: The 11 hospitals documented 715 valid observations, and feedback on SSC application was provided for 79% of the observations. In 61%, all team members stopped their work for the SSC application, and in 71%, the items were read off from the checklist (instead of recalled from memory). On average, 86% of the standard items were read out by the checklist coordinator, whilst the two items at Sign Out were read out only in 60% and 74%. Additional visual checks with another source (e.g. patient wristband) took place in only 41%, and verbal confirmation of the items (by someone else other than the checklist coordinator) was obtained on an average of 76% across all three checklist sections. The surgical teams reacted positively in 64% to the peer feedback. Conclusion: Both implementation fidelity and acceptability of the intervention were high—the present intervention seems suitable for regular monitoring of the quality of SSC application with internal resources. Peer observation facilitated identifying weaknesses regarding the SSC process and application at item level. Across all hospitals, the Sign Out section in general, visual control for item checks and lack of work interruption of all team members during SSC application showed up as the main areas of improvement.